Estimating Fixed Points for Suzuki Mappings via New Iterative Scheme - Sabri, Raghad I. (Iraqi Journal of Science, 2026)
The main objective of this paper is to propose a new iterative method for approximating fixed points of a type of mapping known as Suzuki mappings. Important convergence results of the proposed method are also studied. To support the main results of this work, a numerical example is presented where the numerical results show that the new method is better than many other methods in terms of its convergence to the fixed point.